(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
Water or food restriction is among the most frequently used motivational operations in studies of basic processes of operant learning in laboratory animals. The aim of the present study was to investigate systematically the body weight development of rats submitted to controlled water or food restriction for about 7 months, as compared to animals under an ad Lib regimen. Brief occasional interruptions of the restriction schedule were carried out. Subjects were 29 Wistar rats bred at the Experimental Psychology Department Animal House. They were weighed daily from Day 5 to Day 217 after birth. In the first experimental phase, all animals had ad Lib access to water and food for 106 days. In the second phase, from Day 107 to Day 217, subjects were divided in three groups. Animals in the Ad Lib group (n = 10) had permanent access to both water and food; animals in the Water Restriction group (n = 10) had daily access to 23 ml water and free access to food, whereas subjects in the Food Restriction group (n=9) were allowed daily access to 17 g of food and free access to water. During this phase, there were two interruptions in the restriction regimen, lasting 15 and 5 days. Results showed a positive though slow acceleration of body mass during the first month after birth, followed by a relatively more rapid increase tending to asymptotic values. After the restriction schedules started on Day 107 body weight declined gradually. Interruptions in the restriction procedure resulted in increased body weight, which was more pronounced after the second interruption. In addition, after each interruption, a greater resistance to body weight loss was observed. The data illustrate the general pattern of body mass acquisition in rats, in the presence and absence of water or food restriction, along a period corresponding to a typical behavioral experiment. They can thus be useful as experimental parameters in future experiments.